Tio2 mediated photocatalytic inactivation of gram-positive and gram-negative bacteria using fluorescent light - Pal, Amrita (2006)
Photocatalytic inactivation of six different species of bacteria using fluorescent light and TiO2 was conducted. Up to five surface loadings of TiO2 varying from 234-8662 mg/m2, impregnated on membrane filters were used with fluorescent light of constant illuminance of 3900 Lux for the inactivation of four ATCC bacteria (E. coli K-12, Pseudomonas fluorescens, Bacillus subtilis and Microbacterium sp.) and two other species of bacteria (Microbacteriaceae str. W7 and Paenibacillus sp. SAFN-007) collected from outdoor air in Singapore. A Gram-negative bacterium E. coli K-12 was the most effectively inactivated, while Gram-positive Bacillus subtilis exhibited the least response to the photocatalytic treatment. The inactivation rate increased with an increase in the TiO2 loading, the maximum inactivation of most bacteria was achieved at an optimum TiO2 loading of 1116-1666 mg/m2. 100% of the E. coli K-12 was inactivated after 30 minutes of treatment at a TiO2 loading of 1666 mg/m2, while inactivation of one log10 was obtained for Microbacterium sp., Paenibacillus sp. SAFN-007 and Microbacteriaceae str. W7 after two hours. Preliminary experiments indicate that the photocatalytic inactivation using Degussa P25 is 1.83-5.41 times higher than that of Hombikat UV-100.